Pembuatan Aplikasi Login dan Mewarnai Menggunakan MIT App Inventor - Wilia Zulkifni Amanda, Sularno (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2024)
Mobile applications have become an integral part of our daily lives, offering a wide range of functionalities from entertainment to productivity. One platform that facilitates the creation of mobile applications is MIT App Inventor, which enables users to design and develop Android applications through an intuitive, block-based programming interface. This journal discusses the development of two simple applications using MIT App Inventor: a login application and a coloring application. The login application is designed to authenticate users before allowing access to specific content, ensuring security and controlled access within the app. This feature is critical in many applications to protect sensitive information and provide a personalized user experience. The second application, a coloring app, is designed to offer an interactive and creative experience for users by allowing them to color various images. This type of application is not only entertaining but also educational, as it can help users, especially children, in developing their fine motor skills and color recognition abilities. The coloring app includes features such as selecting different colors and drawing on a canvas, making it engaging and easy to use for people of all ages. The development process for both applications is detailed, including the design of the user interface and the implementation of key functionalities using MIT App Inventor's block-based programming environment. For the login application, the focus was on creating a secure and user-friendly authentication process, while for the coloring application, the emphasis was on providing a smooth and enjoyable drawing experience.